Syntheses, Characterization And Biological Activities Of New Hydrazinyl Thiazolyl Coumarin Derivatives - Arshad, Afsheen (2011)
Coumarin and thiazole are two important pharmacophores, the syntheses of which acquire great importance in medicinal chemistry due to the diverse pharmacological activities. The present study aims to synthesize some (45) new biologically active compounds by incorporating thiazole ring with coumarin nucleus. Two new series of hydrazinyl thiazolyl coumarin derivatives have been synthesized in four steps. The first step of the synthesis was the preparation of acetyl coumarins by Knoevenagel’s condensation of substituted salicyaldehydes with ethyl acetoacetate in the presence of catalytic amount of piperidine. In the second step, bromination of acetyl coumarins was carried out with bromine in order to yield the corresponding bromoacetyl coumarins. Thiosemicarbazones were synthesized in the third step by treating thiosemicarbazide with various substituted aldehydes and ketones in the presence of a catalytic amount of glacial acetic acid. The final step of the synthesis involved the preparation of two new series of hydrazinyl thiazolyl coumarins using Hantzsch cyclization protocol. One series of compounds was obtained by reacting 3-bromoacetyl coumarins with thiosemicarbazones derived from various substituted aldehydes, while the other series was furnished by treating thiosemicarbazones of substituted ketones with 3-bromoacetylcoumarins. All the synthesized compounds were fully characterized by IR, 1H and 13C NMR, elemental analysis and mass spectroscopy.